2015
DOI: 10.3103/s1063457615030041
|View full text |Cite
|
Sign up to set email alerts
|

Procedure of the multiple indentations for determination of the hardness parameters of structurally heterogeneous materials

Abstract: A procedure of multiple indentations has been proposed as a promising method of studying surface properties of structurally heterogeneous bodies. It has been shown that this procedure is applicable to a wide spectrum of multiphase (including superhard) materials, ceramics, and metals and makes it pos sible to assess mean properties of separate phases and a composite as a whole as well as a degree of the sam ple hardness inhomogeneity at various scale levels. Such information is important in prediction of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…At this point, we can draw an analogy between the microstructure and mechanics of CNC-epoxy composites and those of biological composites such as bone and nacre, which are largely composed of brittle constituents, and yet display ductile mechanical behavior at larger scales [12]. Here, statistical results from nanoindentation can connect the nanoscale mechanical behavior to the micro-mechanical properties of the CNC-epoxy composites, by relating the indentation depth to the intrinsic length scale of the microstructure of the material [47]. Indentation at shallow depth allows individual phases in the sample microstructure to be resolved, while deep indents provide averaged values representative of the macroscopic mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, we can draw an analogy between the microstructure and mechanics of CNC-epoxy composites and those of biological composites such as bone and nacre, which are largely composed of brittle constituents, and yet display ductile mechanical behavior at larger scales [12]. Here, statistical results from nanoindentation can connect the nanoscale mechanical behavior to the micro-mechanical properties of the CNC-epoxy composites, by relating the indentation depth to the intrinsic length scale of the microstructure of the material [47]. Indentation at shallow depth allows individual phases in the sample microstructure to be resolved, while deep indents provide averaged values representative of the macroscopic mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that adding Cr increases the contact thermal conductivity of diamond-binder interface tenfold, from 2.1·10 6 to 2.3·10 7 W/(m 2 •K) [14] being typical value for chemical bonding case [15]. [16], which consists in conducting a series of tests ( fig. 9) followed by statistical processing of the obtained indentation curves ( fig.…”
Section: Dcm Characterizationmentioning
confidence: 99%
“…In the same way, heterogeneous anisotropic composites such as layered or coated materials present a similar problem, being the thin films a clear example of this behaviour [15]. Moreover, even for phases whose properties can be determined in bulk specimens, their characteristics when included in a composite are often somewhat different from material characteristics in bulk pieces [16][17][18]. Thus, in many cases the mechanical characterization of the constituent phases, in order to deduce their contribution to the overall behaviour of the composite, obviates conventional mechanical testing of large representative specimens.…”
Section: Introductionmentioning
confidence: 99%
“…the slope of the initial portion of the unloading curve, employing the Oliver-Pharr method [19]. Extensive work has been dedicated to extract the local mechanical characteristics of ceramics from the loading-unloading curves [13][14][15][16][17][18][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation